2017
DOI: 10.1007/s10461-017-1692-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Receiving Late HIV Testing Among Women Delivering at Hung Vuong Hospital, Ho Chi Minh City, Vietnam, 2014

Abstract: HIV testing during pregnancy facilitates timely antiretroviral treatment for HIV-positive women. This study identifies reasons for late HIV testing among pregnant women delivering at a hospital in Ho Chi Minh City. We conducted a case-control study in which 160 cases were women who were tested for HIV late (i.e., at labor and delivery) and 160 controls were women who were tested during antenatal care (ANC). In multivariable logistic regression analysis, six variables were associated with late HIV testing: age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
2
13
1
Order By: Relevance
“…This could be attributed to the fact that sexual education tends to be focused on young women who may be involved in high-risk sexual behaviors and that older women do not perceive themselves to be at risk for HIV [ 27 , 38 , 39 ]. These findings are consistent with studies from Vietnam, Ethiopia, and 11 East African countries, which also reported older age to be associated with less HIV testing [ 40 , 41 ]. Nonetheless, further studies should be conducted to critically identify reasons why older women (35 years and above) are less likely to test for HIV during pregnancy in Rwanda.…”
Section: Discussionsupporting
confidence: 90%
“…This could be attributed to the fact that sexual education tends to be focused on young women who may be involved in high-risk sexual behaviors and that older women do not perceive themselves to be at risk for HIV [ 27 , 38 , 39 ]. These findings are consistent with studies from Vietnam, Ethiopia, and 11 East African countries, which also reported older age to be associated with less HIV testing [ 40 , 41 ]. Nonetheless, further studies should be conducted to critically identify reasons why older women (35 years and above) are less likely to test for HIV during pregnancy in Rwanda.…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the fact that sexual education tends to be focused on young women who may be involved in high-risk sexual behaviours [29,30]. These ndings are consistent with studies from Vietnam and Ethiopia which also reported older age to be associated with less HIV testing [31,32]. Nonetheless, further studies should be conducted to critically identify reasons why older women (35 years and above) are less likely to test for HIV during pregnancy in Rwanda.…”
Section: Discussionsupporting
confidence: 64%
“…Study ndings also indicate that non-working pregnant women had higher odds of HIV testing compared to those working. This deviates from study ndings in Vietnam and Ethiopia which reported employed pregnant women being more likely to test for HIV [31,40]. Although employment is a vital component of women's empowerment for making healthy decisions and choices, it has also been reported to have a negative effect on other women's health aspects, predisposing women to sexual violence [41] and reducing antenatal and postnatal care attendance [42,43] partly due to the busy work schedules.…”
Section: Discussioncontrasting
confidence: 58%